Analysis of the Effect of Work Flexibility and Work Stress on Remote Worker Performance Mediated by Work Motivation - Rizky Aditya Dwi Prakoso Pudjiharto; Gunarianto (Journal of Management Research and Studies, 2024)
The aim of the research is to obtain empirical evidence regarding the influence of work flexibility, work stress and work motivation on the performance of Remote Worker employees in XX Malang City. Also to obtain empirical evidence regarding the influence of work flexibility and work stress mediated by work motivation on the performance of Remote Worker employees in XX Malang City. And finally, this research also aims to obtain empirical evidence regarding the influence of work flexibility and work stress on the work motivation of Remote Worker employees in XX Malang City. The population in this study were Remote Workers totaling 80 people in XX Malang City. Because this is a census research, the number of samples taken is as large as the existing population, namely 80 Remote Worker employees in XX Malang City. The data analysis method uses descriptive statistics and verification analysis using a variance-based Structural Equation Model or called Partial Least Square (PLS), which consists of validity tests, reliability tests and hypothesis testing techniques. The research results show that work flexibility, work stress and work motivation have a significant and positive effect on employee performance in XX Malang City. Work flexibility and work stress have a significant effect on performance which is mediated by full work motivation (full mediation). Work flexibility and work stress have a significant effect on work motivation.